Educating creatively gifted students in Ibadan metropolis (2019)
Numerous problems confronting the human race require creative interventions in order to make living conditions meaningful, comfortable and impactful. Creative solutions are significantly of utmost necessity because rigours of diverse kinds are meant to be reduced to the barest minimum. However, gifted students whose innovative endowments are expected to be exploited to advantage are uncatered for in Nigerian schools, most especially in Ibadan Metropolis. The creatively gifted students' potentially inventive prowess has not been put to expression simply because appropriate educational or instructional strategies have not been professionally adopted by the school system. The children need differentiated learning experiences and activities, which include brainstorming, bibliotherapy, questioning/lateral thinking approach, synectics, ability grouping, independent study among a host of other techniques. The teacher and resource person who facilitates the education of the children has some pedagogical roles to play to be able to handle the children effectively. The teacher should utilize the recommended instructional strategies to achieve the desired result among the students. The teacher is expected to adopt such instructional packages to meet the learning needs, styles and abilities of creatively gifted students. By virtue of such enrichment, the students can explore their creative instincts.